Advances and Directions in Preschool Mental Health Research. (9th January 2015) - Dougherty, Lea R.; Leppert, Katherine A.; Merwin, Stephanie M.; Smith, Victoria C.; Bufferd, Sara J.; Kushner, Marissa R.
Abstract Over the last decade, researchers have expanded our understanding of early‐emerging mental health problems in preschoolers. In this article, we review the epidemiology, course, and clinical significance of disruptive behavior disorders, attention deficit hyperactivity disorder, anxiety disorders, and depressive disorders in preschoolers. We present findings highlighting advances in preschool psychopathology and treatment research, and provide directions for the field of preschool mental health. To understand preschool psychopathology, we need to take an empirically based, developmentally sensitive approach that includes understanding more fully both normative and atypical development. Such an approach will inform how we define, assess, and treat early mental health problems.